2012
DOI: 10.1227/neu.0b013e31823209cf
|View full text |Cite
|
Sign up to set email alerts
|

JS-K, a Glutathione S-Transferase–Activated Nitric Oxide Donor With Antineoplastic Activity in Malignant Gliomas

Abstract: Background Glutathione S-transferases (GSTs) control multidrug-resistance and are upregulated in many cancers including malignant gliomas. The diazeniumdiolate JS-K generates nitric oxide (NO) on enzymatic activation by glutathione and GST, showing promising NO-based anticancer efficacy. Objective To evaluate the role of NO-based antitumor therapy with JS-K in U87 gliomas in vitro and in vivo. Methods U87 glioma cells and primary glioblastoma cell lines were exposed to JS-K and a variety of inhibitors to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 50 publications
5
54
0
Order By: Relevance
“…In contrast to our previous studies in orthotopic intracranial and flank-tumor rat models which demonstrated a moderate effect of NO donor compounds (JS-K, PABA/NO) on tumor growth, cell proliferation, survival, and tumor physiology, no significant in vivo antitumor effect could be observed in this orthotopic U87 xenograft mouse model. 13,14,38,39 Several facts might contribute to this result. First, in this study, JS-K was applied intravenously (i.v.)…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast to our previous studies in orthotopic intracranial and flank-tumor rat models which demonstrated a moderate effect of NO donor compounds (JS-K, PABA/NO) on tumor growth, cell proliferation, survival, and tumor physiology, no significant in vivo antitumor effect could be observed in this orthotopic U87 xenograft mouse model. 13,14,38,39 Several facts might contribute to this result. First, in this study, JS-K was applied intravenously (i.v.)…”
Section: Discussionmentioning
confidence: 95%
“…The antitumor effect of JS-K could be confirmed in other glioma cell lines in vitro. 14,22,23 Multiple reasons underlie the strong therapy resistance of GBM cells: these include the accumulation of mutations that result in the increased expression of antiapoptotic and tumorigenic factors, deregulation or block of apoptosis inducing pathways, upregulation of enzymes essential for DNA repair, that is, O(6)-methylguanine-DNA methyltransferase (MGMT), or cell detoxification, as GSTs, and hypoxic conditions within the tumor area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, a site-specific NOreleasing compound that could be activated in glutathione (GSH)-expressing cells, showed improvement in duration time and treatment efficacy (Weyerbrock et al, 2012).…”
Section: Site-specific Delivery Of Controlled No-releasing Agentmentioning
confidence: 99%
“…Similar to excess Glutamate, SAS targets the antioxidant xCT-system and the resulting pharmacologic effect is reported to improve antitumor efficacy of COX inhibitors in in vivo models of tumorigenesis [51] [52]. As a clinically approved xCT inhibitor [53], SAS is reported to inhibit GSH formation or the activation of AKT and focal adhesion kinases [54] [55]. SAS has been used as an effective inhibitor of tumor growth and tumor-associated seizures, particularly for the inflammatory brain tumor [56].…”
Section: Cbx and Sulfasalazine (Sas) Drug Combination Treatmentmentioning
confidence: 99%